KERTAS INDIKATOR BUNGA BELIMBING WULUH (AVERRHOA BILIMBI L) UNTUK UJI LARUTAN ASAM-BASA (Jurnal Pendidikan Madrasah, 2016)
This article aims at making and using indicatorpaper from natural materials flower starfruit (Averrhoa bilimbi L). Indicators are made of filter paper soaked in flower extracts starfruit, and dried. Excellence indicators: easily observed, sparing use, practical, and cheaper. Indicator papers tested in a solution of citric acid, sodium bicarbonate, and sodium chloride. Tests on citric acid showed a bright red color change, sodium carbonate showed blue-green discoloration, and the sodium chloride does not change color. Based on the findings, it was concluded that the interest starfruit can be made indicator in the form of paper, and can be used as an acid-base media lab at the class of 7th of IPA in MTsN Giriloyo.